PENGARUH CURRENT RATIO (CR), RETURN ON ASSET (ROA), DAN PRICE EARNINGS RATIO (PER) TERHADAP HARGA SAHAM PT BUMI SERPONG DAMAI Tbk PERIODE 2013-2022 - Daffa Earin Alghazali; Hasudungan Pangaribuan (Journal of Research and Publication Innovation, 2025)
The aim of this research is to determine the influence of the Current Ratio, Return On Assets, and Price Earnings Ratio on the share price of PT Bumi Serpong Dami tbk for the 2013-2022 period. This research was conducted with historical data using a time series design. This research uses a descriptive and quantitative approach with classical assumption testing methods, hypothesis testing, t tests, F tests, and data analysis techniques using multiple linear regression. The results of this research are that the Current Ratio partially has a significant effect on stock prices according to the value tcount > ttable or (3.021 > 2.36462). This is also reinforced by the value ρvalue < Sig. 0.050 or (0.023 < 0.050), the t value is positive, so it can be interpreted that the Current Ratio has a positive and significant effect on changes in stock prices. Partial Return on Assets does not have a significant effect on share prices according to the value of tcount < ttable or (0.332 < 2.36462). This is also reinforced by the value ρvalue > Sig. 0.050 or (0.751 > 0.050), the t value is positive, so it can be interpreted that Return On Assets has no significant effect on changes in stock prices. The Price Earnings Ratio partially has no significant effect on stock prices according to the value of tcount < ttable or (1.307 < 2.36462). This is also reinforced by the value ρvalue > Sig. 0.050 or (0.239 > 0.050) is a positive t value, so it can be interpreted that the Price Earnings Ratio has no significant effect on changes in stock prices. Simultaneously the Current Ratio, Return on Assets and Price Earnings Ratio partially have no significant influence on share prices according to the Fcount <Ftable or (5.644 < 4.350), this is also confirmed by ρvalue < Sig. 0.050 or (0.035 < 0.050), the Fcount value is positive, so it can be interpreted that the Current Ratio, Return on Assets and Price Earnings Ratio have a positive and significant effect on changes in stock prices.